Alimentação saudável na infância: as representações sociais de pais e/ou responsáveis e de escolares do primeiro ano do ensino fundamental - Silveira, Cláudia Lilian Witt da (Universidade do Vale do Rio dos Sinos, 2013)
The study aimed to understand social representations about healthy eating in childhood of families with school-age children in São Leopoldo/RS. It was a 128 qualitative multiple study-case, using semi-structured interviews with parents and children's drawings. Participated in this study eight families from low socioeconomic class, among whom five had food safety and three had unsafe food indicators. Qualitative content analysis revealed that the history of countryside eating habits was remembered by parents during their childhood as a difficult time, but healthier than current habits, when fast-foods, industrialized foods and sweets are more accessible. Although the families’ knowledge, rooted in its own history and updated by scientific discourse, have pointed toward a healthy eating, both proximal and distal strengths push their eating habits on other direction. The easy access to unhealthy foods and, on the other hand, financial constraints and the scarcity of healthy food options close to home, were linked with the busy life of families and the pleasure associated with "junk food" consumption as a way out of routine and to get satisfaction, generating several impasses in adopting healthier eating. These findings indicate the need for a more holistic and comprehensive approach, not just based on strategies focused in individual education and counseling, but targeting different contexts of sociability of the child in order to incorporate healthier eating habits as something pleasant and accessible in family routine.
Healthy eating in childhood: social representations of families and children in school age
Keywords: Alimentação saudável; Escolares; Família; Representações sociais; Healthy eating; School age; Family; Social representation; ACCNPQ::Ciências da Saúde::Saúde Coletiva